Synthesis and thermoelectric properties of Re3As6.6In0.4 with Ir3Ge7 crystal structure - Verchenko, Valeriy Y.; Vasiliev, Anton S.; Tsirlin, Alexander A.; Kulbachinskii, Vladimir A.; Kytin, Vladimir G.; Shevelkov, Andrei V. (Beilstein Journal of Nanotechnology, 2013)
The Re3As7−xInx solid solution was prepared for x ≤ 0.5 by heating the elements in stoichiometric ratios in evacuated silica tubes at 1073 K. It crystallizes with the Ir3Ge7 crystal structure, space group Im−3m, with a unit-cell parameter a ranging from 8.716 to 8.747 Å. The crystal structure and properties were investigated for a composition with x = 0.4. It is shown that indium substitutes arsenic exclusively at one crystallographic site, such that the As–As dumbbells with dAs–As = 2.54 Å remain intact. Re3As6.6In0.4 behaves as a bad metal or heavily doped semiconductor, with electrons being the dominant charge carriers. It possesses high values of Seebeck coefficient and low thermal conductivity, but relatively low electrical conductivity, which leads to rather low values of the thermoelectric figure of merit.
Keywords: band-structure calculations; energy conversion; Ir3Ge7 type; solid solution; thermoelectric material